2003
DOI: 10.1086/378614
|View full text |Cite
|
Sign up to set email alerts
|

How Good Gets Better and Bad Gets Worse: Understanding the Impact of Affect on Evaluations of Known Brands

Abstract: for their support during the research process. The author also acknowledges the University of Illinois marketing, social cognition, and affect groups for their help during the research process and the editor, associate editor, and reviewers of this article for their thoughtful comments. The research and writing for this project was supported by funds from the J. M. Jones Chair at the University of Illinois and research grants (HKUST6053/01H and DAG00/01.BM49) from the Hong Kong Research Grants Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 46 publications
3
86
1
Order By: Relevance
“…Bless & Fiedler, 2006;Schwarz & Clore, 2006) or overly positive evaluations of options (e.g. Adaval, 2003;Bower, 1991;Howard & Barry, 1994). A closer look at the data revealed, however, that positive affect was related to search in older but not younger adults.…”
Section: Discussion Of Studymentioning
confidence: 99%
“…Bless & Fiedler, 2006;Schwarz & Clore, 2006) or overly positive evaluations of options (e.g. Adaval, 2003;Bower, 1991;Howard & Barry, 1994). A closer look at the data revealed, however, that positive affect was related to search in older but not younger adults.…”
Section: Discussion Of Studymentioning
confidence: 99%
“…This confirmatory search results in a strong correlation between the immediate affective response elicited by a target and the spontaneous thoughts that people associate with the target. 4 This strong correlation in turn results in more polarized evaluations (Adaval, 2003). Consistent with this proposition, Pham et al, (2001) found, for instance, that affective feelings toward a variety of stimuli (magazine pictures, TV commercials, etc.)…”
Section: Properties Of Evaluations and Decisions Based On Integral Afmentioning
confidence: 70%
“…On the one hand, they seem to promote greater flexibility and creativity in problem solving; on the other hand, they seem to promote a more top-down, less data-driven, and less thorough mode of processing. Recent studies by Adaval (2003) suggest that one consequence of this more top-down form of processing is that positive moods polarize the evaluative impact of judgment inputs involving preexisting knowledge structures (e.g., schemata, stereotypes, categories, brands, etc.). Adaval's (2003) studies show that, under positive mood, brand names (and their associated knowledge structures) have greater influence on product evaluations than under negative mood.…”
Section: Effects Of Incidental Affect On Judgment and Decision Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies should examine the influence of the emotional context on the effectiveness of TVCs that induce positive or negative emotions on their own; TVCs of well-known brands that elicit a rich network of mental associations (Adaval, 2003), and effectiveness of TVCs that are already familiar to the participants. Finally, the durability of the effects of the emotional context on advertising effectiveness should also be examined.…”
Section: Discussionmentioning
confidence: 99%